Analisis Perlindungan Bagi Konsumen Dalam Transaksi Digital Menggunakan Transaksi Digital cryptocurrency bitcoin - Nessa Lendrawati; M.Arafat Hermana; Ferawati Royani (JURNAL HUKUM SEHASEN, 2026)
The development of digital technology has given rise to cryptocurrency as a new investment instrument. In Indonesia, cryptocurrency is not recognized as a legal means of payment but is classified as a commodity supervised by the Badan Pengawas Perdagangan Berjangka Komoditi (BAPPEBTI), which raises legal issues related to consumer protection in volatile and high-risk transactions.mThis study aims to analyze the legal position of consumers, the forms of legal protection available, and the roles of business actors and supervisory authorities using a normative legal research method. The findings show that consumer protection for crypto assets has not been specifically regulated and still relies on general regulations. Bank Indonesia prohibits the use of cryptocurrency as a means of payment, while BAPPEBTI supervises its trading as a commodity. However, supervision and dispute resolution mechanisms remain limited, resulting in suboptimal legal certainty for consumers.